The Influence of Customer Value and Service Quality on Customer Loyalty Mediated by Customer Satisfaction at BRI Bank, Tabanan Branch Office - Ni Kadek Intan Milinia Purwani; Ni Putu Nita Anggraini; Agus Wahyudi Salasa Gama (International Journal of Economics and Management Sciences, 2025)
Customer loyalty is a crucial pillar in the banking industry, especially amidst increasingly fierce competition and rapid digital transformation. Loyalty not only reflects brand attachment but also reflects the level of customer trust and satisfaction with the services provided. This study aims to analyze the role of customer value and service quality in building customer loyalty, with customer satisfaction as an intervening variable. The study was conducted at the BRI Tabanan Branch using a quantitative approach. The research sample consisted of 383 respondents selected using the Krejcie and Morgan formula. Data were collected through questionnaires, interviews, and documentation, then analyzed using path analysis to examine the direct and indirect relationships between variables. The results show that customer value and service quality significantly influence customer satisfaction. Both variables also have a direct effect on customer loyalty, while also exerting an indirect effect through customer satisfaction as a mediating variable. In other words, increasing perceived value and service quality not only drives satisfaction but also strengthens loyalty, both directly and through the effects of satisfaction. These findings emphasize the importance of strategies to increase value and service quality as an effort to maintain loyalty amid changing customer preferences and digital disruption. For banking practitioners, the implications of this research can serve as a reference in designing more personalized, value-oriented, and technology-based service programs to increase long-term customer retention and strengthen competitiveness in an increasingly competitive market.